2015
DOI: 10.1016/j.jsha.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Polycythemia vera presenting as acute myocardial infarction: An unusual presentation

Abstract: Acute myocardial infarction (AMI) is usually seen in the setting of atherosclerosis and its associated risk factors. Myocardial infarction in the young poses a particular challenge, as the disease is less likely, due to atherosclerosis. We report the case of a 37-year-old female patient who presented with ST segment elevation anterolateral AMI. The only abnormality on routine blood investigation was raised hemoglobin and hematocrit. After further testing, she was diagnosed according to the World Health Organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…It is often diagnosed incidentally on a routine laboratory testing prior to a major thrombotic event. However, myocardial infarction as the initial manifestation of PV as in our patient is unusual [2][3][4][5][6][7][8][9]. Although hyper viscosity is commonly considered to be the major pathogenic mechanism for arterial thrombotic complications in PV, a significant number of patients have other risk factors like smoking, hypertension, arguing strongly in favor of additive risk and shared pathogenesis [10].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is often diagnosed incidentally on a routine laboratory testing prior to a major thrombotic event. However, myocardial infarction as the initial manifestation of PV as in our patient is unusual [2][3][4][5][6][7][8][9]. Although hyper viscosity is commonly considered to be the major pathogenic mechanism for arterial thrombotic complications in PV, a significant number of patients have other risk factors like smoking, hypertension, arguing strongly in favor of additive risk and shared pathogenesis [10].…”
Section: Discussionmentioning
confidence: 89%
“…It is therefore important to consider pre-procedure phlebotomy to achieve a goal hematocrit of 45% whenever possible. There is limited data on use of other revascularization methods such as fibrinolysis or coronary artery bypass surgery in these patients [3,7,8]. A brief review on the management of acute MI in patients with PV from published case reports in english literature is shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Inami et al, [ 15 ] reported that similar thrombus occlusion at proximal LAD which managed through primary PCI with Bare Metal Stent stenting resulted in acute stent thrombosis as an outcome. Interestingly, the good outcome was observed on the thrombolysis treatment on a patient with extensive anterior STEMI and PV, [ 14 ] also on the conservative treatment of a patient with anterior STEMI and PV. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Here, we present a case of a patient with PV, who had massive coronary artery thrombosis presenting with sudden cardiac arrest. Although there have been many similar case reports [16], none have described an ST elevation myocardial infarction with ventricular fibrillation arrest presentation nor the extent of arterial thrombosis observed in this patient and its unique management.…”
Section: Introductionmentioning
confidence: 92%